LEXICAL AND SEMANTIC FEATURES OF LINGUISTIC MEANS RELATED TO PARTS OF WIND MUSICAL INSTRUMENTS (PROCEEDINGS OF THE NATIONAL ACADEMY OF SCIENCES OF THE KYRGYZ REPUBLIC, 2025)
The article reveals the linguistic function of words related to parts of wind instruments in the Kyrgyz language. Characterized by the lexical meanings of such parts of wind instruments as head, hole, ring, mouth, eye, whistle, mouthpiece, notch, slot. The connection between lexical components and their function is considered. The relationship of words related to musical instruments to the names of parts of the human body, used products, clothing and other types of musical instruments is determined. It is noted that wind instruments are among the ancient instruments that in ancient times performed such an important function as transmitting messages and signals in everyday life. The connection of words related to parts of Kyrgyz national wind musical instruments with their direct meanings is determined.
Keywords: head, hole, ring, mouth, eye, whistle, mouthpiece, recess, gap, lace